Variation of minimum safety separation for non-conducting lightning targets - Nourirad, Ghasem; Izadi, Mahdi; Gomes, Chandima; Ab Kadir, Mohd Zainal Abidin (2014)
The minimum separation between a human body and 10 m high objects struck by lightning, to avoid side flashes, has been studied. Objects with different materials and cross sectional areas have been considered. The parameters of lightning current waveform used in this paper are those pertinent to negative subsequent strokes given in IEC 62305-1 (2010). Since the minimum separation between a human being and an object struck by lightning is related to human safety, the worst case scenarios are considered. The distance between a two meter tall human being and the object struck by lightning is varied and the distribution of electric field around the object was calculated. Consequently, we computed the minimum separation between the human body and the lightning struck object with a range of values of resistivity and cross sectional area so that the probability of side flashing during a lightning strike have been discussed.